PENGARUH PELATIHAN DAN PENGEMBANGAN KARYAWAN TERHADAP KINERJA PEKERJA DI PUSAT KEBUGARAN F45 TRAINING CABANG CILANDAK - Riska Rismayanti; Shella Puspita Sari (Journal of Research and Publication Innovation, 2025)
The aim of this research is to determine the effect of employee training and development and worker performance both partially and simultaneously at the F45 Training Cilandak Fitness Center. This research method uses quantitative methods with a descriptive approach. The collection methods used are primary data and secondary data. The sampling technique in this research used the Saturated Sampling Technique of 60 respondents. Data analysis uses the SPSS version 26 program application. The analysis techniques used are validity test, reliability test, classical assumption test, normality, multicollinearity test, heteroscedasticity test, simple linear regression analysis, multiple linear regression analysis, correlation coefficient test, coefficient of determination test and hypothesis test. Testing the hypothesis above obtained t count > t table (6.028 > 1.997). So it can be concluded that H0 is rejected, H1 is accepted, which means that there is an influence between Cilandak. obtained t count > t table (3.166 > 1.997).This is also strengthened by the significance of <0.050 or (0.000 <0.05). So it can be concluded that H02 is rejected. Ha2 is accepted, which means that there is an influence between X2 and Y or shows that there is a partially significant influence between employee development on worker performance at the F45 fitness center Cilandak Branch Training.So it can be concluded that the influence of employee training and development simultaneously has a significant effect on employee performance (Y). Determination obtained by Adjusted R Square The value of the coefficient of determination or contribution of influence simultaneously is 35.9% while the remaining 64.1% is influenced by other factors. Meanwhile, the remaining 42.3% was influenced by other factors not examined in this study.